TINJAUAN YURIDIS TERHADAP PERLINDUNGAN HUKUM BAGI PENGGUNA JASA PINJAMAN ONLINE ILEGAL DI INDONESIA - Pratama Sinaga, Eko; Alhakim, Abdurrakhman (UNES Law Review, 2022)
Looking at the development of technology that is so fast and also used in all fields to provide convenience. This also includes electronic transactions on online loan applications (pinjol), given the current economic conditions that are not in a good condition due to Covid-19, many people choose loan applications to meet their needs without seeing the overall consequences of their actions. The case of a pinjol application that attacks the personal data of its users is of course a prohibited act because it is related to someone's personal data. This study aims to find out how the legal protection for illegal loan service users in Indonesia is and what are the obstacles to law enforcement in dealing with loan lending cases in Indonesia. This research uses normative legal research methods. And it is known that in Indonesia, about criminal law policies that can be used to punish debtors for their actions, they can use UUPK because of the position of borrowing users as consumers and use the ITE Law because transactions are carried out using electronic media. The obstacles that occur are the lack of experts in the field of electronics in law enforcement and also the ITE Law is not strong enough to ensnare borrowers.